(3OjhGf HGeNQeIs - (3YeQ Hf YHO Gddg HGeNQeI GdgLQGfj GdTjHGfj GdMVQej,J (B952 (3g` s ((3eMeO Hf YhV Hf WjH s)
(3ChdgG (B:s
(3MQa GdHGA GdehMOI jG bVjH GdPgH Tfa dj GdcGS HGTQH dG JNGa GdYJH eG aj GdJeNdGY eYJH s
(3BNQgG (B:s
(3bd bO aYdJ aEfj Hc hGKb hHeje eLOc bO hUdJ MHGdj s
(3fSNI KGfjIs
(3hocJHJ GdYfGhjf HGdMeQIs
(3egOGI Edi GdSdWGf UGdM Hf ZGdH GdbYjWjs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs